Mountain gorillas benefit from social distancing too: Close proximity from tourists affects gorillas' sociality. Issue 1 (11th December 2022) - Costa, Raquel F. P.; Romano, Valéria; Pereira, André S.; Hart, Jordan D. A.; MacIntosh, Andrew; Hayashi, Misato
Abstract: Gorilla tourism supports the protection of its ecosystem, benefiting humans and wildlife populations living therein. Assessing to what degree the presence and proximity of tourists affect wildlife aids long‐term benefits. Because wild animals might see human activities as stressors, we hypothesized that the increased presence and proximity of tourists leads to immediate changes in gorilla social cohesion. We constructed social networks from association rates before, during, and after tourist visits, and when tourists were very close (≤3 m) or close (>3 m) to them. Our analysis focused on this distance threshold (≤3 m and >3 m) because the 7 m rule, enforced by the national park, was violated 84% of the time. We showed that gorillas spent more time in closer association after tourists arrived and when tourists were <3 m away from gorillas. Immediate changes were detected in the number of individuals close to each other, the time they spent together and the distance of an individual to all others, indicating that gorillas might increase social cohesion because they perceive tourists as a risk. These results highlight the need to enforce the tourism guidelines (maximum of eight people per group, including park staff; minimum distance of 7 m) to ensure the sustainable success of gorilla tourism. Abstract : Immediate changes were detected in the number of individuals close to each other, the time they spent together and the distance of an individual to all other individuals indicating that gorillas might increase social cohesion because they perceive tourists as a risk. These results highlight the need to enforce the tourism guidelines (maximum of eight people per group, including park staff, and a minimum distance of 7 m).